Impedance based bolt pre-load monitoring using piezoceramic smart washer - Huo, Linsheng; Chen, Dongdong; Liang, Yabin; Li, Hongnan; Feng, Xin; Song, Gangbing (Smart materials and structures, 2017)
Bolted connection is widely used in mechanical and civil engineering; however, in some cases, bolt looseness may cause catastrophic consequences. Bolt pre-load monitoring in real time can help to ensure the safety of component connections and durability of the entire steel structure. Previous research has demonstrated that a 'smart washer (SW)' fabricated by embedding a piezoceramic transducer into two flat metal rings could effectively detect the pre-load looseness of a bolted connection. The active sensing method, in which two SWs are necessary, was used in the previous research. In this research, an electro-mechanical impedance (EMI) method enabled by one 'SW' was developed to investigate the pre-load condition of a bolted connection. Since the installed SW is directly subjected to the same axial pre-load as that on the bolt, the piezoceramic SW with the EMI technique is uniquely suited for pre-load monitoring of a bolted connection. The pre-load reduction is directly reflected by the EMI of the piezoceramic SW. In particular, a decrease of the pre-load on a bolt connect results in the reduced of its resonant frequency, which can be revealed by the real part of the impedance. In addition, the root mean square deviation (RMSD) of the impedance signals was employed as an index to evaluate the bolt looseness degree. For the experimental study, a bolted connectional specimen with a piezoceramic SW was fabricated and investigated. In the experiment, eleven cases of different pre-loads on the bolt were studied. Experimental results clearly show that with the decrease of the bolt pre-load, the resonant frequency of the bolt joint also decreased, as reflected by the impedance of piezoceramic SW. In addition, experimental results demonstrated that the SW with the EMI based RMSD index can monitor bolt pre-load.